2000
DOI: 10.1046/j.1365-2923.2000.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and drug use in second-year medical students at the University of Leeds

Abstract: 86% of the students drank alcohol and among those who drank, a high proportion (52.6% of the men and 50.6% of the women), exceeded the recommended weekly limit of alcohol consumption of 21 units for men and 14 units women per week). Illicit drug use was reported by 33.1% of students (28.3% of men, 35.6% of women). The drug most commonly used was cannabis. According to the Hospital Anxiety and Depression (HAD) scale, 41.2% of the students (37% of men, 43.3% of women) had anxiety ratings within the clinically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
3
22

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(147 citation statements)
references
References 4 publications
8
108
3
22
Order By: Relevance
“…Students who chose this functional coping strategy preferred less dysfunctional strategies such as alcohol and drugs. Alcohol and drug abuse among practicing physicians [49,50] and medical students [5153] is supported by literature. Up to 20% of medical students have reported excessive alcohol consumption [5456].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Students who chose this functional coping strategy preferred less dysfunctional strategies such as alcohol and drugs. Alcohol and drug abuse among practicing physicians [49,50] and medical students [5153] is supported by literature. Up to 20% of medical students have reported excessive alcohol consumption [5456].…”
Section: Discussionmentioning
confidence: 98%
“…The use of illicit drugs by medical students is similar to that of age-related peers, and studies indicate that students who use these drugs had started using them before they entered medical school [57,52,58]. Pickard and colleagues [53] found a higher risk of alcohol consumption among Leeds medical students than among the age-matched population. 53% of men and 51% of women regularly exceeded the recommended amount of alcohol per week, while in a sample population in the 18–24 age group only 41% exceeded the safe limit indicated by the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…dIscussIon Alcohol, tobacco, and psychotropic drug use is a worldwide health problem, which has prompted a wealth of studies on the issue. University students 19,20 , including medical students, are affected by substance use [6][7][8][9][10][11][12][13][14][15][16]21 . In researching the issue, one must take particular care to avoid generalizing data analyzed from a preconceived standpoint, particularly in light of cultural, political, and social stances towards psychotropic substance use [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…Due to their knowledge of and ease of access to various drugs, physicians and medical students have been assessed as a possible target of substance abuse [1][2][3][4][5][6][7][8][9][10][11] . The high rate of psychotropic drug use among physicians is a well established fact 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Surveys of medical students have been more prevalent over the last 20 years and give similar cause for concern. [8][9][10][11][12][13][14][15] The effects of excessive alcohol intake and use of illicit drugs have obvious potential consequences for the careers of dentists. Recent studies have shown that, following graduation, alcohol and drug habits either remain high, 7 or decrease, but remain 'at a level where personal harm is possible' .…”
mentioning
confidence: 99%